Effects of rebars on the detectability of subsurface defects in concrete bridges using square pulse thermography. (December 2018) - Tran, Quang Huy; Huh, Jungwon; Mac, Van Ha; Kang, Choonghyun; Han, Dongyeob
Abstract: The ability to predict critical conditions on highway concrete bridges is important for the avoidance of unpredictable collapses during the operation period. Potential deteriorations can develop, such as terms of cracks, air voids, and subsurface delaminated areas that are usually detected through nondestructive testing (NDT) techniques together with conventional sounding methods, i.e. hammer sounding and chain dragging. Of these deteriorations, delamination is one of the major indicators of concrete bridge health, i.e., the measurement of the percentage of delaminated area. Due to vehicle loading, changes in weather and environment, and corrosion of reinforcing steel bars, delamination can occur above or even below the rebar layer, and it can be difficult to identify and determine the size and depth of delamination, especially for delamination below the rebars. In this study, two concrete specimens were analyzed in the laboratory as used with a wide range of different concrete covers that are commonly applied in bridge structures, from 2 to 8 cm at near surface. Square Pulse Thermography (SPT), one of the active infrared thermography (IRT) techniques, is used to analyze the specimens in terms of their various heating regimes and environmental conditions. This study aims to comprehensively investigate the effect of steel reinforcement on the detectability of delamination when the delaminations have a width-to-depth ratio equal to or smaller than 2.0. The results show that delamination above the rebars indicates a higher absolute contrast than that below the rebars. In addition, the observation time of delamination below the rebars decreases significantly. As a result, the predicted depth of a delamination will be less than the value of the real depth.